Copper‐Catalyzed Chemoselective O‐Aroylation of Phenolic Oxime Ethers with Aryl Aldehydes. Issue 16 (27th April 2021) - Kumar, Upendra; Sharma, Ajay; Kumar, Naveen; Kumar Pandey, Satyendra
Abstract: Copper‐catalyzed oxidative O ‐aroylation of phenolic oxime ethers with a wide range of aromatic aldehydes are described. This approach offers an efficient synthesis of phenolic oxime ether esters in good to excellent yields. Abstract : Copper‐catalyzed oxidative O ‐aroylation of phenolic oxime ethers with a wide range of aromatic aldehydes are described. This approach offers an efficient synthesis of phenolic oxime ether esters in good to excellent yields.